Problemas ambientais decorrentes da ocupação subnormal na bacia do Jaguaribe - João Pessoa-PB - Queiroz, Degner Rodrigues de Almeida (2009)
One of the problems found in João Pessoa City is the disordered population growth in risky areas and in areas protected by specific legislation, the so-called Subnormal Clusters which, in a general way, is connected to social factors. In the face of this reality, it is necessary to do a bibliographical survey about topics related to socioenviromental and infrastructural aspects that exist at Jaguaribe Basin, area of study, in order to propose the management and planning for river basins through the proposal of actions for several problems, respecting the difficulties and peculiarities of the area, as well as, the integration of scientific and public documents related to the theme, having as the main aim to understand the dynamics of the urban environment and the existing public policies, integrating the various factors that stimulate the area of study.